Reformulasi Pengaturan Penambangan Bawah Laut di Wilayah Perairan Indonesia - Puspitawati, Dhiana; Minahasa Putra, Teddy; Vandy Wardana, Rangga (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 10 No 4 (2021)DO - 10.24843/JMHU.2021.v10.i04.p05, 2021)
Ocean is the largest place where natural resources can be found. With the continuing decrease of land resources, nations are now lying their hopes to the ocean in providing more natural resources.  As the largest archipelagic state in the world, Indonesia is blessed with rich ocean resources. United Nations Convention on the Law of the Sea 1982 (UNCLOS 1982) provides comprehensive provisions in ocean usage, and principally divides ocean space into various maritime zones, which include zones under national jurisdiction and beyond national jurisdiction. Furthermore, with regard to ocean mining, coastal states should also regulate nationally their ocean mining both on waters under their jurisdiction and beyond their jurisdiction. This research focuses on ocean mining in the ocean space within national jurisdiction of Indonesia. Using normative method, this research finds that although there has been Mining Act in Indonesia, however, provisions on ocean mining needs to be reformulated. While there has been Presidential Regulation which regulates ocean sand mining, it is argued that ocean resources not only consist of sand. Thus, this research recommends reformulation of national regulations on Mining that is to include ocean mining; and distinguish between ocean mining in ocean within and outside national jurisdiction. In addition, it should also provides for and clustering other ocean resources and not only limited to ocean sand mining. United Nations Convention on the Law of the Sea 1982 (UNCLOS 1982) membagi wilayah laut kedalam zona-zona maritim lengkap dengan ketentuan tentang hak dan kewajiban negara pantai dan negara pengguna, pada masing-masing zona maritime tersebut. Berkaitan dengan penambangan bawah laut, tentu saja jika dilakukan di wilayah territorial Indonesia, maka Indonesia mempunyai kedaulatan penuh dalam pemanfaatan sumber daya laut yang terkandung di dalamnya. Dengan menggunakan metode yurisdis normatif, tulisan ini akan menganalisa apakah pengaturan penambangan bawah laut di Indonesia telah membedakan antara wilayah perairan dan wilayah diluar yurisdiksi Indonesia. Tulisan ini menemukan bahwa meskipun Indonesia sudah mempunyai hukum nasional tentang penambangan, khususnya tentang mineral dan batubara, akan tetapi belum secara eksplisit mengatur tentang eksplorasi dan eksploitasi sumber daya mineral di laut; dan belum memisahkan antara wilayah perairan didalam dan di luar yurisdiksi nasional Indonesia. Oleh karena itu, tulisan ini merekomendasikan reformulasi pengaturan penambangan bawah laut di wilayah perairan Indonesia. Pengaturan penambangan bawah laut di wilayah perairan Indonesia juga harus mengatur penggolongan (klasterisasi) sumber daya mineral di wilayah perairan Indonesia.